Current practices regarding discourse analysis and treatment following non-aphasic brain injury: A qualitative study. (11th June 2015) - Maddy, Katherine; Howell, Dana; Capilouto, Gilson
Abstract : Discourse production deficits are a common feature of non-aphasic brain injury (NABI). However, little is known about current practices of speech-language pathologists in the assessment and treatment of discourse production deficits following NABI. A phenomenological approach of inquiry was used to examine the experiences of speech-language pathologists in the assessment and treatment of individuals with NABI, with a particular focus on discourse production deficits. Nine speech-language pathologists participated in semi-structured individual interviews. Participants identified common discourse production deficits and hypothesized about the impact on a person's quality of life. However, external influences negatively impacted participants' practice regarding discourse assessment and treatment. External influences included time constraints, lack of standardized data, and the lack of formalized education regarding discourse assessment and treatment. These findings suggest that there is a discrepancy between speech-language pathologists' values and their actual clinical practice related to the analysis and implementation of treatment for discourse production deficits.